2023
DOI: 10.1002/adma.202211143
|View full text |Cite
|
Sign up to set email alerts
|

Perspiring Soft Robotics Skin Constituted by Dynamic Polarity‐Switching Porous Liquid Crystal Membrane

Abstract: Secretion of functional fluids is essential for affecting surface properties in ecosystems. The existing polymer membranes that mimic human skin functions are limited to secreting, either apolar or polar, liquid. However, the development of membranes that grant exchange liquid with different polarities remains a grand challenge. This process is prohibited by the mismatch of the polarity between the carrier polymer and the loaded liquid. To conquer this limitation, an innovative strategy is reported to dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Besides secreting 5CB, our coating has the potential of secreting various liquids (Figure S17, Supporting Information), which branches out the application in the biological field. [22] We anticipate our "perspiring" LCN fingertips can be applied in robotic devices to induce greater biomimicry of the human body, thus boosting their anthropopathic function development in the future, e.g., pick and place function, self-cleaning, drugs delivery, and information transfer between robots.…”
Section: Discussionmentioning
confidence: 99%
“…Besides secreting 5CB, our coating has the potential of secreting various liquids (Figure S17, Supporting Information), which branches out the application in the biological field. [22] We anticipate our "perspiring" LCN fingertips can be applied in robotic devices to induce greater biomimicry of the human body, thus boosting their anthropopathic function development in the future, e.g., pick and place function, self-cleaning, drugs delivery, and information transfer between robots.…”
Section: Discussionmentioning
confidence: 99%
“…[ 115 ] An understanding of the reaction dynamics of droplet reactors on open surface platforms is necessary, but still represents a significant challenge. The design of functional active open surfaces represents an opportunity to make strides in this area. Advanced open surface platforms: Although many open solid and liquid surfaces have been reported as functional platforms for droplet reactors, [ 131,198,211–213 ] the development of advanced open surface platforms with muti‐functional characteristics, such as active open surfaces for different chemical feeding rates, still needs consideration. Application area: Recent studies have reported that droplet reactors on open surfaces can be used in bioanalysis, [ 214 ] drug release, [ 215 ] pollutant removal, [ 216 ] and 3D printing. [ 217 ] Despite extensive progress, the application area of droplet reactors on open surfaces should be further investigated, with emphasis on high temperature reactions, [ 19 ] catalysis, [ 48 ] novel material synthesis, [ 48 ] and other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their intrinsic properties, including maintaining mixtures of positional and orientational order in various mesophases, [167] immobilized LCs have been exploited for a variety of applications, including display technology, [168,169] sensors, [170][171][172][173][174][175][176] particle self-assembly, [177][178][179][180][181][182][183][184][185] molecular assembly [186][187][188] and synthesis, [189][190][191][192][193][194] and activating the release of cargo. [195][196][197][198][199][200][201] Very recently, our group reported a class of LC-infused porous surfaces as advanced open anisotropic liquid surfaces for droplet reactors (Figure 14A). [113] An important feature for the design of this open surface is the ability to manipulate the chemical compositions of resting droplets through controlling the chemical release from open functional surface to droplets.…”
Section: Droplet Reactors On Anisotropic Liquid-infused Porous Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous bioactive/immunomodulatory molecules to facilitate stem cell differentiation [15] or immunomodulation. [16] State-of-the-art chemical release systems, such as the layer-by-layer assembly of polymers, [15,17] phospholipid cubosomes, [18] hydrogel, [5,12,14,19] and water microdroplets dispersed in liquid crystal (LC) surfaces, [20] can perform only one type of release at a time. The simultaneous release from a single material system of the same or different chemicals in both an on-demand pulsatile and a continuous mode has been a substantial challenge.…”
Section: Introductionmentioning
confidence: 99%